A Proposal for a Next Generation European Neutron Source. (September 2016) - Andersen, K.H.; Carlile, C.J.
Abstract: We argue that it is not too early to begin the planning process for a next generation neutron source for Europe, even as the European Spallation Source is being constructed. We put forward three main arguments. Firstly, nowadays the period between the first scientific concept of a new facility being proposed and its actual realisation is approaching half a century. We show evidence for this. Secondly, there is a straightforward development of the short pulse/long pulse spallation concepts that will deliver gains in neutron brightness of more than a factor 30 over what the ESS will soon deliver and provide the optimum balance between resolution and intensity. We describe our concept, which is a spallation source where the proton pulse length is matched to the moderating time of slow neutrons. Thirdly, when we look at our colleagues in astronomy and high energy physics, we see that they have a totally different, more global and more ambitious approach to the coming generations of large facilities. We argue that it is time for the neutron community not simply to rest upon its laurels and take what is given but to be proactive..